2019
DOI: 10.21597/jist.481990
|View full text |Cite
|
Sign up to set email alerts
|

4-Benzilidenamino-4,5-dihidro-1H-1,2,4-triazol-5-on Türevlerinin Antioksidan Aktivitelerinin Teorik Olarak İncelenmesi

Abstract: Bu çalışmada, antioksidan özellikleri deneysel olarak belirlenmiş bazı 4-benzilidenamino-4,5-dihidro-1H-1,2,4-triazol-5-on türevleri bileşiklerinin Yoğunluk Fonksiyonel Teorisi yöntemiyle antioksidan etkinliklerinin karşılaştırılması yapılmıştır. Yoğunluk fonksiyonel teorisine (DFT) dayanan kuantum kimyasal hesaplamalar, deneysel sonuçlarında en fazla ve en az antioksidan aktiviteye sahip 4-benzilidenamino-4,5-dihidro-1H-1,2,4-triazol-5-on türevlerinin (2a ve 2g için) arasındaki ilişkiyi incelemek için kullanı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
(2 reference statements)
0
4
0
1
Order By: Relevance
“…Although there are no experimental data for FTIR, the computational values available can be considered significant due to the compatibility between the experimental and computational NMR data, which will be seen in the following sections. Even so, some important points should be underlined [33,34]. 1-The peak, which refers -O-H group's stretching, appears in 3629 cm −1 , 3884 cm −1 , 3393 cm −1 and 3124 cm −1 (mode 195), according to method, respectively [35].…”
Section: Ft-ir Vibrational Analysismentioning
confidence: 99%
“…Although there are no experimental data for FTIR, the computational values available can be considered significant due to the compatibility between the experimental and computational NMR data, which will be seen in the following sections. Even so, some important points should be underlined [33,34]. 1-The peak, which refers -O-H group's stretching, appears in 3629 cm −1 , 3884 cm −1 , 3393 cm −1 and 3124 cm −1 (mode 195), according to method, respectively [35].…”
Section: Ft-ir Vibrational Analysismentioning
confidence: 99%
“…Therefore, it is important to investigate the boundary MOs of a molecule and to know which atoms contribute to these orbitals. The most important reason for this is; reactivity centers are determined by these energy schemes (Turhan Irak et al, 2019;Fukui, 1982).…”
Section: Frontier Orbitalsmentioning
confidence: 99%
“…If the predicted frequencies are scaled to account for the approximation handling of electron correlation, for basis set shortcomings, and for the anharmonicity, density functional theory calculations (DFT) are said to provide excellent vibrational frequencies of organic compounds [49,50]. Several publications in the literature have discussed the calculation of the chemical shift of the Nuclear Magnetic Rezonans using quantum-chemistry techniques [51][52][53][54][55]. However, it was suggested that the single-point calculation of magnetic shielding by DFT methods was combined with a quick and accurate geometry-optimization procedure at the molecular mechanics level because as molecular size increases, computing-time limitations are introduced for obtaining optimized geometries at the DFT level [51].…”
Section: Introductionmentioning
confidence: 99%